2018
DOI: 10.1016/j.jmr.2018.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Efficient GPU-based Monte-Carlo simulation of diffusion in real astrocytes reconstructed from confocal microscopy

Abstract: The primary goal of this work is to develop an efficient Monte-Carlo simulation of diffusion-weighted signal in complex cellular structures, such as astrocytes, directly derived from confocal microscopy. In this study, we first use an octree structure for spatial decomposition of surface meshes. Octree structure and radius-search algorithm help to quickly identify the faces that particles can possibly encounter during the next time step, thus speeding up the Monte-Carlo simulation. Furthermore, we propose to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 39 publications
(66 reference statements)
0
28
0
Order By: Relevance
“…In 54 we performed an accuracy and computational timing study of the serial SpinDoctor finite element simulation and a GPU implementation of the Monte Carlo simulation. 32 We showed that at equivalent accuracy, if only one gradient direction needs to be simulated, SpinDoctor is faster than GPU Monte Carlo. Because the GPU Monte Carlo method is inherently parallel, if many gradient directions need to be simulated, there is a break-even point when GPU Monte Carlo becomes faster than SpinDoctor.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…In 54 we performed an accuracy and computational timing study of the serial SpinDoctor finite element simulation and a GPU implementation of the Monte Carlo simulation. 32 We showed that at equivalent accuracy, if only one gradient direction needs to be simulated, SpinDoctor is faster than GPU Monte Carlo. Because the GPU Monte Carlo method is inherently parallel, if many gradient directions need to be simulated, there is a break-even point when GPU Monte Carlo becomes faster than SpinDoctor.…”
mentioning
confidence: 90%
“…The first group is referred to as Monte Carlo simulations in the literature and previous works include References. 4,[28][29][30][31] A GPU-based acceleration of Monte Carlo simulation was proposed in References 32,33 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There might be a number of recent works with similar goals, this study however has some improvements such as successful simulation of permeability instead of assuming all microstructural walls are impermeable compared to [82] or lack of requirement any complex mathematical and time-consuming construction of microstructure such as in [63] and instead direct simulation of microsture from light microscopy data.…”
Section: Six Plates (Voxel)mentioning
confidence: 99%
“…The first group is referred to as Monte-Carlo simulations in the literature and previous works include [13,[24][25][26][27]. A GPU-based acceleration of Monte-Carlo simulation was proposed in [28,29]. Some software packages using this approach include 1.…”
Section: Introductionmentioning
confidence: 99%